2021
DOI: 10.1111/ijcs.12720
|View full text |Cite
|
Sign up to set email alerts
|

How to craft humorous advertisements across diverse cultures? Multi‐country insights from Brazilian, Chinese and American consumers

Abstract: In today's multicultural environment, the influence of cultural orientations on humorous advertising outcomes is increasingly significant for researchers and practitioners. Drawing on a theoretical framework from culture dimensions and theories of humour in advertising, this research examines the moderating role of cultural orientation on the relationship between humour styles and consumers' attitudes towards humorous ads. Empirical results from studies conducted in Brazil, China and the United States show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
(173 reference statements)
0
6
0
Order By: Relevance
“…Sixth, humour is a culturally bounded phenomenon in that the content of popular or appreciated humour varies widely across cultures (Crawford & Gregory, 2015), such that what is considered as funny in one country may not be well received in another country (Duncan, 1982). For instance, Zhu et al (2022) find that consumers from collectivistic cultures (e.g., China, Brazil) demonstrate more favourable attitudes towards and perceive greater humour from ads using affiliative humour than those from individualistic cultures (e.g., United States, Sweden). Since this study was conducted in the United States, where the individualistic culture is prevalent, it is worth investigating whether the effects found in this study persist across different countries and cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixth, humour is a culturally bounded phenomenon in that the content of popular or appreciated humour varies widely across cultures (Crawford & Gregory, 2015), such that what is considered as funny in one country may not be well received in another country (Duncan, 1982). For instance, Zhu et al (2022) find that consumers from collectivistic cultures (e.g., China, Brazil) demonstrate more favourable attitudes towards and perceive greater humour from ads using affiliative humour than those from individualistic cultures (e.g., United States, Sweden). Since this study was conducted in the United States, where the individualistic culture is prevalent, it is worth investigating whether the effects found in this study persist across different countries and cultures.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Zhu et al (2022) find that consumers from collectivistic cultures (e.g., China, Brazil) demonstrate more favourable attitudes towards and perceive greater humour from ads using affiliative humour than those from individualistic cultures (e.g., United States, Sweden). Since this study was conducted in the United States, where the individualistic culture is prevalent, it is worth investigating whether the effects found in this study persist across different countries and cultures.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…In addition, social exchange theory has been widely adopted to examine attitudes in relational societies such as China (Shore et al, 2009;Duan et al, 2022). Collectivism is one of China's most widely researched cultural characteristics (Zhu et al, 2022;Zhang et al, 2022), which can also be used to distinguish between individuals in the same cultural context. Thus, as an individual variable, collectivism may moderate the relationship between perceived CSR and job performance (via perceived organizational support), in line with social exchange theory.…”
Section: Social Exchange Theorymentioning
confidence: 99%
“…Lascu et al (2016), for example, compared online fashion magazine advertisements in France and the USA in terms of needs appeals, emotional appeals, and sex appeals and found that emotional advertising was more preponderant in French advertisements, whereas sexual advertising was more preponderant in US advertisements. Zhu et al (2022) studied the moderating role of cultural orientation on the relationship between humor styles and consumers' attitudes towards humorous ads and found that consumers from individualist-collectivist and with high/low uncertainty avoidance countries have different favorable attitudes towards and perceive greater humor from affectevoking humorous ads. Ashraf et al (2020) examined corporate and product advertising by examining consumer ad involvement (AI) levels (a motivational state activated by the personal relevance of stimuli and found that developed market consumers (USA) tend to be as involved with corporate ads as they are with product ads, whereas emerging market consumers (Pakistan) are more involved with product ads than with corporate ads.…”
Section: Advertising Research In Cross-cultural Contextmentioning
confidence: 99%
“…Zhu et al. (2022) studied the moderating role of cultural orientation on the relationship between humor styles and consumers' attitudes towards humorous ads and found that consumers from individualist–collectivist and with high/low uncertainty avoidance countries have different favorable attitudes towards and perceive greater humor from affect‐evoking humorous ads. Ashraf et al.…”
Section: Literature Reviewmentioning
confidence: 99%